Manufacturing and Characterization of High Impact Polystyrene (HIPS) Reinforced with Treated Sugarcane Bagasse - Benini, Kelly Cristina Coelho de Carvalho; Voorwald, Herman Jacobus; Cioffi, Maria Odila Hilá¡rio (Journal of Research Updates in Polymer Science, 2017)
Natural fibers obtained from sugarcane bagasse were used as reinforcement for high impact polystyrene (HIPS) composites. Fibers were chemically treated with an alkaline solution and then bleached with sodium chlorite and acetic acid, in order to remove amorphous constituents and improve adhesion with polimeric matrix.The alkali-treated and bleached fibers over a range of 10-30 wt% were mixed with HIPS and placed in an injector chamber in order to obtain tensile and flexural test specimens. Chemical treatment effects on composites properties were evaluated through mechanical tests and thermal and microscopy analysis. Experimental results show that composites with 30 wt% of alkali-treated fibers present an improvement in the tensile strength (17%), tensile modulus (96%) and flexural modulus (34%) with a consequent decrease in the ductility and in the thermal properties in comparisson to pure HIPS. An huge increase of 191% in the flexural modulus for composites with 30 wt% of bleached fibers was obtained compared to pure HIPS.